2023
DOI: 10.17762/ijritcc.v11i6.6767
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Encryption of Cloud Processing With IOT Devices Using DNA And RSA Cryptography

Sohit Agarwal,
Gagan Joshi

Abstract: The research paper titled "Hybrid Data Encryption as well as Decryption Using Hybrid RSA and DNA" develops a hybrid cryptosystem by combining the usefulness of such an asymmetric-key (public-key) cryptosystem with the efficacy of a symmetric-key (private-key) cryptosystem. These two types of cryptosystems use different types of keys. The method addresses concerns regarding the users' right to privacy, authentication, and accuracy by utilizing a data encryption process that is secure in both directions. Both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Results concluded that utilizing the integrating Rivest-Shamir-Adleman (RAS) cryptosystem and block cipher ensured secure transmission with improved accuracy compared to traditional methods. Agarwal and Joshi [15] presented a hybrid cryptosystem for merging asymmetric RSA (ARSA) and symmetric DNA encryption (SDNAE). Further, the present method also addresses authentication, privacy, and efficiency issues, thereby providing proven sustainability for cloud-based internet of things (IoT) processing.…”
Section: Introductionmentioning
confidence: 99%
“…Results concluded that utilizing the integrating Rivest-Shamir-Adleman (RAS) cryptosystem and block cipher ensured secure transmission with improved accuracy compared to traditional methods. Agarwal and Joshi [15] presented a hybrid cryptosystem for merging asymmetric RSA (ARSA) and symmetric DNA encryption (SDNAE). Further, the present method also addresses authentication, privacy, and efficiency issues, thereby providing proven sustainability for cloud-based internet of things (IoT) processing.…”
Section: Introductionmentioning
confidence: 99%